Digital literacy of an EFL teacher in IT-based language instruction to teach speaking - Williyan, Aldha; Taufiqi, Muhammad Aulia; Kurniadi, Didit (Universitas Aki, 2025)
Learners in today's modern age are highly technologically savvy. It is no surprise that some forms of IT-based instruction are used in language courses to make classes more entertaining and participatory for students. Teachers can involve their students in the learning process by providing a vibrant and engaging classroom environment using technology. This research aims to investigate the level of digital fluency of an Indonesian EFL teacher who uses IT-based language instruction to teach speaking, as well as how the Indonesian EFL teacher integrates digital tools and technology in their language instruction to teach speaking skills. These goals are achieved by observing an EFL teacher and 37 EFL students during three sessions of the teaching and learning process using a qualitative methodology. The results show that IT-based instruction is delivered through a variety of applications and websites, demonstrating the high level of digital literacy of the EFL teacher. It also reveals that the learning process is now inextricably linked to the internet as a learning resource and instrument, and that technological advancements benefit both students and teachers. Therefore, it is challenging to separate the roles of teachers and technology in constructing the current educational paradigm due to their influence on its progress.